The role of PRP in the healing of disc degeneration and the effect of local anesthetics on PRP - Mert, Ahmet; Ikinci Keles, Ayse; Aydin, Murat; Erol, Huseyin Serkan; Sonmez, Osman Fikret (Frontiers in Bioengineering and Biotechnology, 2025)
AimThis study aimed to investigate the regenerative effects of PRP on an experimental rat model of disc degeneration using histological and biochemical parameters. Additionally, we evaluated whether ropivacaine, a local anesthetic commonly used in clinical practice, affects the efficacy of PRP.MethodsRats were randomly divided into five groups as control and treatment groups. Disc degeneration models were established using appropriate procedures. On the intervention day, PRP was prepared from whole blood collected from the rats. PRP, PRP + ropivacaine, or ropivacaine alone was administered at the appropriate doses and according to standardized protocols.ResultsIn the untreated disc degeneration groups, annulus fibrosus (AF) and nucleus pulposus (NP) boundaries were indistinct, disc morphology was disrupted, collagen structures in the AF were degenerated or irregular, and vacuolization, interstitial edema, and necrotic tissue remnants were observed in the NP region. In contrast, in groups treated with PRP and PRP + ropivacaine, a reduction in edema and vacuolization, disappearance of necrotic tissue, restoration of distinct NP and AF boundaries, and decreased atrophy and cellular clustering in NP cells were observed. Biochemical analysis showed that IL-6 and TNF-α levels were within normal ranges in the groups treated with PRP and PRP + ropivacaine, whereas these levels remained elevated in the untreated disc degeneration groups, indicating ongoing effects of degeneration.ConclusionThis study demonstrates the regenerative effects of PRP in disc degeneration through histological and biochemical parameters. Furthermore, the addition of ropivacaine to PRP did not exert any negative effects on PRP’s regenerative properties.